2017
DOI: 10.1177/1558944717708032
|View full text |Cite
|
Sign up to set email alerts
|

Fixation Strength in Full and Limited Fixation of Osteoporotic Distal Radius Fractures

Abstract: There was no difference detected between osteoporotic intra-articular distal radius fractures treated by utilizing all 7 of the distal screws of a volar plate compared with those treated with only 4 distal screws.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…In the distal radius fracture plate, nine screws were used, six of which were in the distal volar plate. Mansuripur et al investigated the effect of the number of screws used on the outcome [ 10 ]. There is not any significant differences when seven screws were compared to four, but the higher the number of screws there is the higher risk of extensor irritation and intra-articular placement [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the distal radius fracture plate, nine screws were used, six of which were in the distal volar plate. Mansuripur et al investigated the effect of the number of screws used on the outcome [ 10 ]. There is not any significant differences when seven screws were compared to four, but the higher the number of screws there is the higher risk of extensor irritation and intra-articular placement [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mansuripur et al investigated the effect of the number of screws used on the outcome [ 10 ]. There is not any significant differences when seven screws were compared to four, but the higher the number of screws there is the higher risk of extensor irritation and intra-articular placement [ 10 ]. For osteoporotic intra-articular distal radius fracture managed with a volar plate and submaximal distal screws, Mansuripur et al showed that the construct is stable enough for early postoperative rehabilitation [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first is biomechanical and cadaveric research that demonstrated sufficient strength of volar locking plates in withstanding the forces of daily activities during early rehabilitation, in both extra-and intra-articular fractures. [35][36][37][38][39][40][41][42] The second is observational and surgical studies where light daily activity was advocated early after surgery with a splint removed. [43][44][45][46][47] Collectively, these studies corroborate the findings of the review that early performance of daily activities, without a splint is safe and is accepted clinical practice in many centres.…”
Section: Discussionmentioning
confidence: 99%